The Artistic Practices With Feminist Approaches As Educational Experiences That Promote Social Transformation - García-Huidobro-Munita, Rosario (2020)
The present article seeks to describe artistic practices that incorporate a feminist perspective in initial university formation and to reflect on how students make links between arts, teaching, and feminist thought as a contribution to their professional development and that of the students at school. For this, the learning experience of a group of students from the career of Pedagogy in Art Education, at Silva Henríquez Catholic University, is collected. During the Integral Workshop course, they carried out works of artistic creation with a feminist approach and linked their works with didactic activities involving gender and social transformation aspects in the classroom. We postulate that the transit between the artistic and the pedagogical fields that they study in the university formation allows the development of a political commitment as artists-educators. This commitment shows other ways of teaching arts in the classroom, where they demonstrate a feminist position of education and pedagogical relationships. These principles would bring us closer to teachings that make the artistic practice adopt a stand in favor of transformative experiences, which go beyond the school curriculum to open spaces for dialogue and understanding in school.